Practice and proficiency of Isha Yoga for better mental health outcomes: insights from a COVID-19 survey - Malipeddi, Saketh; Mehrotra, Seema; John, John P.; Kutty, Bindu M. (Frontiers in Public Health, 2024)
Introduction The COVID-19 pandemic has brought about unparalleled suffering on a global scale, affecting both physical and mental well-being. In such challenging times, it becomes crucial to identify interventions that can alleviate negative mental health outcomes, such as stress, while promoting positive mental health outcomes, like well-being. We report the effectiveness of a mind–body practise, Isha Yoga, in promoting well-being. Methods We conducted an online survey, during the COVID-19 pandemic, with Yoga practitioners (n = 1,352) from the Isha Yoga tradition in Karnataka, India. We evaluated stress and well-being attributes using conventional psychometric questionnaires. Subsequently, we requested the Isha Yoga practitioners to share another survey with their friends and family members, assessing similar outcomes. From the respondents of this shared survey (n = 221), we identified individuals who currently did not engage in any form of Yoga or meditation, constituting the non-Yoga control group (n = 110). To enhance the reliability and validity of our study and minimize the limitations commonly associated with online surveys, we adhered to the CHERRIES guidelines for reporting survey studies. Results Isha Yoga practitioners had significantly lower levels of stress (p < 0.001, gHedges = 0.94) and mental distress (p < 0.001, gHedges = 0.75) while reporting significantly higher levels of well-being (p < 0.001, gHedges = 0.78) and affective balance (p < 0.001, gHedges = 0.80) compared to the control group. Furthermore, expertise-related improvements were observed in these outcomes, and a dose–response relationship was found between regularity of Isha Yoga practice and outcome changes. A minimum 3–4 days of weekly practice showed significant differences with the control group. In addition, we investigated the effect of Isha Yoga on stress and well-being among the healthcare workers (HCWs) in our sample and observed better mental health outcomes. Discussion These findings collectively underscore the benefits of Mind and Body practices like Isha Yoga on various aspects of mental health and well-being, emphasizing its potential as an effective and holistic approach for promoting a healthy lifestyle among diverse populations, including healthcare workers, even in difficult circumstances such as the COVID-19 pandemic.